Análise epistemológica do conceito "DNA lixo" sob uma ótica Fleckiana e sua difusão em materiais didáticos - Gregório, Jennifer Gabaldo (Universidade Federal de São Carlos, 2023)
In this work, there is an epistemological analysis of the concept of “junk” DNA, based on the aspects proposed by the biologist Ludwik Fleck, as following: styles of thinking; harmony of illusions; intra-collective and inter-collective circulation of ideas. Furthermore, five textbooks proposed in the Brazilian National Book and Didactic Material Program (PNLD) were selected to understand the effectiveness and dynamics of the dissemination of scientific knowledge about the non-coding regions of DNA, in textbooks used in basic education, and the relevance of the history and philosophy of science (HFC), in line with Fleck's perspective of popular science. The contents analyzed referred to the non-coding regions of DNA, based on the following aspects: the presence or absence of the concept "junk DNA"; the presence of historical contextualization of the theme; and the presence of historical inconsistencies, considering the sociocultural formation of knowledge. Therefore, the research methodology adopted was a qualitative model. For the analysis of the concept, the technique used was the document analysis of articles, and for the analysis of the contents, focusing on the theme “junk DNA”, the analysis of textbooks was carried out. The development of this work involved the consideration that changes in the teaching of science are constant due to changes in the historical-social context in which academic knowledge is constituted. The likelihood of scientific concepts is estimated through historically constructed explanatory models, emphasizing the importance of the history and philosophy of science (HFC) as a didactic possibility in education. Among the books selected to compose this analysis, none of them satisfactorily addresses the historical context that permeates the non-coding sequences of proteins. The book "Natural Sciences - Technological World and Applied Sciences" (2020), by Lopes and Rosso, is one of the most discussed on the subject. In contrast, the book “Biologia Moderna” (2016), by Amabis and Martho, is the least developed, still presenting arguments that may lead to contradictions with current scientific discoveries. The analysis of the books shows a mismatch between the intra-collective and inter-collective circulation of ideas. In the course of the educational process, students should be encouraged to actively participate in the construction of knowledge, considering the historical, political, social, and economic aspects that constitute it, contributing to the development of critical views on the most varied subjects The theme “non-coding regions” selected to compose this discussion is current and is related to the emergence of the area of epigenetics. Therefore, there is still a reflection on the importance of discussing epigenetic processes, influenced by the population´s environmental stimuli and lifestyle habits as well as their role in heredity
Epistemological analysis of the "junk DNA" concept from a Fleckian perspective and its diffusion in didactic materials
Keywords: História e filosofia da ciência; Livro didático; DNA “lixo”; Regiões não codificantes; Epigenética; History and philosophy of science; Textbook; Junk DNA; Non-coding regions; Epigenetics; CIENCIAS BIOLOGICAS::GENETICA